Sclerochronologic and oxygen isotope analysis of growth increments in shells of the bivalve Arctica islandica from southwest off Iceland - Melvik, Vilde (The University of Bergen, 2018)
The marine bivalve mollusc Arctica islandica is presently known as the longest-living non-colonial animal, and considered to be a valuable paleo proxy and recorder of past environmental variability. This study presents the first absolutely dated, statistically robust master shell chronology from the southwest Icelandic shelf (64 °N). The chronology is based on annual growth increments in ten live-collected specimens from the same population, which is combined to form a 141-year long chronology, covering AD 1873-2014. The selected study site is strategically located in the pathway of the relatively warm and saline Irminger Current, a branch of the North Atlantic Current. The Irminger Current carries North Atlantic water masses, and assembling data from A. islandica specimens in this area is therefore a promising tool for the reconstruction of past marine environmental conditions in the North Atlantic beyond instrumental records. The chronology was successfully constructed by sclerochronological procedures, an approach very similar to dendrochronology, by statistical age-detrending, transformation, averaging and standardization of the annual growth increment width series in the selected specimens. Furthermore, inter-annual (intra-incremental) stable oxygen isotope analysis was also performed on three juvenile specimens and enabled estimation of the populations’ main growing season which seems to be between February/March to August/September during which the temperatures were also mostly increasing. Comparisons between the master shell chronology and environmental records, both instrumental and proxy based, from the same region revealed that the growth signal of the population is likely to be directly or indirectly linked to certain environmental factors. Comparison with the growth data indicate that the bivalves are positively linked to the abundance of diatom phytoplankton, and negatively linked to the abundance of herbivorous copepods. These links are, however, probably weakened by the influence of other ...